Reforms of Regional and Agglomeration Railways in Poland – Striving for Sustainable Development of Public Transport - Juliusz ENGELHARDT (Communications of International Proceedings, 2021)
The subject of the considerations presented in the article is a part of the Polish public transport, i.e. passenger, rail regional and agglomeration transport. The research hypothesis of the article is the preliminary assertion that changes in the system of providing regional and agglomeration rail services contributed to the sustainable development of public transport in Poland. Then, the two-stage course of reforms in this field of public transport in the years 2001-2009 was characterized. The analysis of the effects of the changes made positively verifies the research hypothesis - they contributed to a more sustainable development of public transport. In the years 2010-2019, passenger rail transport grew by 81.1 million people, resulting in savings in external transport costs of an estimated € 378.5 million, while the passenger rail sector was financially balanced and does not generate a deficit.
Keywords: Rail Transport; Regional Transport; Agglomeration Transport.